Active zone localization of presynaptic calcium channels encoded by the cacophony locus of Drosophila. - Kawasaki, F.; Zou, B.; Xu, X.; Ordway, R.W. (Journal of Neuroscience, 2004)
Presynaptic calcium channels play a central role in chemical synaptic transmission by providing the calcium trigger for evoked neurotransmitter release. These voltage-gated calcium channels are composed of a primary structural subunit, alpha1, as well as auxiliary beta and alpha2delta subunits. Our previous genetic, molecular, and functional analysis has shown that the cacophony (cac) gene encodes a primary presynaptic calcium channel alpha1 subunit in Drosophila. Here we report that transgenic expression of a cac-encoded alpha1 subunit fused with enhanced green fluorescent protein efficiently rescues cac lethal mutations and allows in vivo analysis of calcium channel localization at active zones. The results reported here further characterize the primary role of cac-encoded calcium channels in neurotransmitter release. In addition, these studies provide a unique genetic tool for live imaging of functional presynaptic calcium channels in vivo and define a molecular marker for immunolocalization of other presynaptic proteins relative to active zones. These findings are expected to facilitate additional analysis of synaptic development and function in this important model system.